PENGEMBANGAN ALAT PERMAINAN EDUKATIF MODEL PEABODY BERBASIS KEARIFAN LOKAL BAGI PENDIDIK PAUD - Asnawi; Mufti Riyani; Hanafiah (LPPM dan PM Universitas Samudra, 2020)
PAUD educators have a strategic role to instill local wisdom owned by the local community through various learning activities and the use of adequate educational teaching aids. But unfortunately PAUD educators still have limitations and obstacles to realize their ideal role. PAUD educators in Darul Aman Subdistrict are more accustomed to using educative teaching aids produced by factories without considering other aspects outside the pragmatic aspects. Community Service aims to assist PAUD Educators in understanding the various types and models of educational game tools and helping educators plan, develop and use Educational tools based on local wisdom. The results of the implementation of activities can increase the linguistic skills of students as has been observed so far not good. produce Educational Game products in the form of hand puppets with the theme of Malem Diwa saga along with a stage and story book as a companion to the Peabody model that was developed based on needs analysis and local wisdom content that is mainstreamed and in accordance with enhanced development aspects. Long term, this service program is expected can foster independence for PAUD Educators in Darul Aman sub-district to be able to develop Educational Games with the same model for other learning themes